The limits to judicial independence: Cambodia's political culture and the civil law. Issue 3 (3rd April 2019) - West, Lucy
ABSTRACT: Distinctions between the common and civil law are crucial when considering the rule of law and judicial independence in a political system. The 1993 Constitution of the Kingdom of Cambodia provides for a democratic government with separation of powers, judicial independence and human rights guarantees consistent with international legal instruments. However, Cambodia ranks poorly in international indices of political interference and corruption in the judiciary and for the rule of law. Drawing on interviews with Cambodian state officials and legal practitioners, the article situates the domestic judiciary within the socio-political environment and constitutional arrangements in which it must operate and examines the limits to judicial independence in the country. The article argues that the lack of judicial independence in contemporary Cambodia is not only attributable to its neopatrimonial political culture but also to the legal-institutional framework established during the United Nations Transitional Authority in Cambodia (UNTAC) period. The legal-philosophical underpinnings of civil law, the nature of the civil law system operating in Cambodia, and how it is interpreted locally, are crucial to understanding the limits to judicial independence in the country.